The combined manifestations of dramatically sore throat, congested and edematous mucosa, no-swelling tonsil are specific in acute Omicron pharyngitis - Lei Zhou; Lineng Zhang; Feng Xu (BMC Infectious Diseases)
Abstract Objective To identify specific clinical signs of Omicron pharyngitis infection. Methods A clinical cross-sectional retrospective study was designed to analyze the primary symptoms of pharyngitis in outpatients seeking treatment for sore throat. Pharyngeal congestion, mucosal edema, were measured using a visual analogue assessment score (0–10) while the presence of ulcers, no-tonsil-swelling, no-tonsil-exudate. They were recorded as "yes" or "no "as two-Categorical data by two senior clinicians, respectively. Significant clinical signs were selected and combined to form a diagnostic panel using SPSS software to differentiate between Omicron pharyngitis and other sore throat cases. The efficiency of the panel was calculated. Results A total of 39 sore throat patients were included in the study, including 15 confirmed cases of Omicron pharyngitis through nuclear acid or Sars-Cov-2 virus antigen testing, and 24 cases of common pharyngitis caused by other pathogens. Mucosal congestion and edema were identified as the most significant symptoms and consolidated into a single working group. When combined with the third significant symptom of no-tonsil-swelling, the three-sign-combined diagnostic panel was found to have a high diagnostic efficiency. Mucosal congestion and edema were the most significant signs. When mucosal congestion and edema were consolidated into a single working panel, the cut-off values were determined to be 7.5 and 1, respectively. When combined with the third significant symptom no-tonsil-swelling, the three-sign diagnostic panel was found to have a high diagnostic efficiency. When compared with the gold standard measurement of Sars-Cov-2 virus antigen or nucleic acid, the diagnostic panel has a sensitivity of 66.7% and a specificity of 91.7%. Conclusion A combination of three signs may be a useful diagnostic tool for Omicron pharyngitis. Clinical signs of dramatic mucosal congestion and edema, non-swollen tonsils are the characteristics of Omicron pharyngitis.